INFLUENCE OF COMPETENCE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE ENGAGEMENT IN GORONTALO CLASS II COMMUNITY CENTER - Musafir, Musafir; Poppy Mu’jizat; Abdul Basid Tuda (Bajang Institute, 2024)
This research aims to provide empirical evidence that competence and organizational culture have a direct influence on employee performance and are mediated by employee engagement at the Gorontalo Class II Penitentiary. All employees were used as a sample of 42 employees. Data collection uses a survey method via questionnaires to all employees. The analysis method used is Path Analysis via SPSS version 22, and uses the Sobel Test to test the influence of employee engagement mediating variables. The research results show that competence has a positive and significant effect on employee performance; Organizational culture has a positive and significant effect on employee performance. Likewise, Employee Engagement is able to mediate significantly between competence and performance, as well as between Organizational Culture and employee performance.